«Nem tudo se pode escrever». Correspondencia diplomática e información «política» en Portugal durante el siglo XVII - Cardim, Pedro (Cuadernos de Historia Moderna, 2006)
This article aims at assessing the role played by correspondence in the diplomatic milieu of the late 17th century. The first part of this essay presents several examples of letter exchange among Portuguese diplomats, in order to demonstrate the importance of correspondence for the diffusion of information, in particular data that had a “political” character. The second part of this article focuses on the ensemble of letters written by Juan Domingo Maserati, diplomat of Charles II of Spain, during his stay in Portugal in the decade of 1670. The in-depth study of this collection of letters shows, in a particularly clear way, how important the letters were as a means of diffusing information about Portuguese politics.